Positive Periodic Solutions of Third-Order Ordinary Differential Equations with Delays - Yongxiang Li; Qiang Li (Abstract and Applied Analysis)
The existence results of positive ω-periodic solutions are obtained for the third-order ordinary differential equation with delays u′′′(t)+a(t)u(t)=f(t,u(t-τ0),u′(t-τ1),u′′(t-τ2)),t∈ℝ, where a∈C(ℝ,(0,∞)) is ω-periodic function and f:ℝ×[0,∞)×ℝ2→[0,∞) is a continuous function which is ω-periodic in t,and τ0,τ1,τ2 are positive constants. The discussion is based on the fixed-point index theory in cones.